Contributions of Educational Institutions in Enhancing Job Skills - Sattar Awad Dhmaid (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Rapid technological change and complex global development challenges require education systems capable of preparing human resources with competencies aligned to sustainable development and evolving labor market demands. Specific Background: Educational institutions are expected to provide academic programs, training systems, and knowledge transfer mechanisms that equip students with employability skills, intellectual capital, and professional readiness. Knowledge Gap: Despite expanding higher education systems, many graduates experience unemployment due to mismatches between institutional educational outputs and labor market requirements, indicating insufficient alignment of curricula, training programs, and stakeholder collaboration. Aims: This study aims to identify the contributions of educational institutions in developing functional skills and supporting graduate employability through educational systems, training mechanisms, and institutional practices. Results: Using a descriptive literature-based methodology, the study finds that educational institutions contribute through human capital development, diversification of educational programs, partnerships with employers, community service initiatives, and knowledge incubator roles; however, outdated curricula, weak communication with labor market stakeholders, and limited focus on personal skills remain significant challenges. Novelty: The study integrates institutional educational functions, employability skills development, and sustainable human resource perspectives into a comprehensive conceptual framework emphasizing coordinated institutional and labor market collaboration. Implications: The findings highlight the necessity for curriculum restructuring, strengthened industry partnerships, continuous graduate engagement, and balanced development of academic and personal competencies to support employment opportunities and sustainable socio-economic development. Highlights: • Educational Systems Require Restructuring to Match Evolving Workforce Competency Expectations.• Institutional Collaboration With Employers Remains Limited Despite Growing Graduate Output.• Knowledge Incubators and Community Programs Support Human Capital Formation Pathways. Keywords: Educational Institutions, Employability Skills, Human Capital Development, Labor Market Alignment, Sustainable Development.